A CLEAR spotlight. Issue 2 (February 2022) - Retallic, Neil; Dutta, Debarun
Abstract : Neil Retallic and Dr Debarun Dutta introduce a forthcoming, exciting new Optician CPD series featuring the BCLA CLEAR reports.